1988
DOI: 10.1007/bf00345506
|View full text |Cite
|
Sign up to set email alerts
|

The human LFA-3 gene is located at the same chromosome band as the gene for its receptor CD2

Abstract: Lymphocyte function-associated antigen 3 (LFA-3) is a widely distributed cell surface glycoprotein that has been assigned a role in cell-cell adhesion on the basis of its capacity to bind to the T-lymphocyte CD2 antigen. The amino acid sequences of the extracellular domains of these two antigens, predicted from their cDNA sequences, show significant similarities, and both are members of the immunoglobulin supergene family. In this communication, a probe prepared from LFA-3 cDNA has been used in Southern blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…The apparent clustering of these related genes raises the possibility that they have been generated by duplication of an ancestral IgSF gene. Other immune cell receptors genes, CD2 and its counter receptor CD58, are also localized in this region (Sewell et al, 1988), in addition to the translocation breakpoint (t(1;22)(p13;q13)) associated with acute megakaryocytic leukemia (Lion et al, 1992).…”
Section: Fig 3 Expression Pattern Of the Gene Igsf3 (A) Northern Bmentioning
confidence: 97%
“…The apparent clustering of these related genes raises the possibility that they have been generated by duplication of an ancestral IgSF gene. Other immune cell receptors genes, CD2 and its counter receptor CD58, are also localized in this region (Sewell et al, 1988), in addition to the translocation breakpoint (t(1;22)(p13;q13)) associated with acute megakaryocytic leukemia (Lion et al, 1992).…”
Section: Fig 3 Expression Pattern Of the Gene Igsf3 (A) Northern Bmentioning
confidence: 97%
“…Additionally, it has been shown that CD2 binds to a second structurally related ligand, human CD48, but with an affinity two orders of magnitude weaker (K d 0 10 −4 M) than that of the CD2-CD58 interaction (K d 0 10 −6 M; Arulanandam et al, 1993a). The CD2, CD58 and CD48 molecules are each thought to have evolved from a common homophilic interaction precursor (Staunton et al, 1987;Sewell et al, 1988;Wong et al, 1990). In the rodent species, CD48 is the only known ligand for CD2 (Kato et al, 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Ofthe 60 metaphases, 25 (41.7%) had a signal at 1p31-32. We note that two structurally homologous members of the immunoglobulin supergene family, lymphocyte function-associated antigen (LFA-3) and CD2 are also found on the short arm of chromosome 1 (31,32). Interestingly, a locus at 1p32, designated T-cell lymphoma 5 (TCLS), may specify a DNA binding protein with a helix-loop-helix domain (33,34).…”
mentioning
confidence: 99%